Dual Use of a Biopolymer From Durian (Durio zibethinus) Seed as a Nutrient Source and Stabilizer for Spray Dried Lactobacillus Plantarum - Lee, Jaslyn J. L.; Zhao, Guili; Kim, Jaejung; Castillo-Zacarias, Carlos; Ramirez-Arriaga, Maria T.; Parra-Saldivar, Roberto; Chen, Wei-Ning (Frontiers in Sustainable Food Systems, 2018)
The search for natural and sustainable biopolymers is increasing. Biopolymers are used in applications, such as to encapsulate and stabilize probiotic bacteria. Currently, this process requires many steps, including the separation of bacteria from the culture media after fermentation, which is energy intensive. In this study, we developed a strategy to use a natural biopolymer from durian seed, durian seed gum (DSG), to address these issues. DSG was used to serve dual roles, firstly as a nutrient source, and secondly as an encapsulating agent. DSG was used in synergy with reconstituted skim milk (RSM), to be a complete nutrient source, for probiotic bacteria Lactobacillus plantarum (L. plantarum). Usually RSM requires supplementation, with costly yeast extract. DSG was characterized to be a suitable nutrient source as it contains polysaccharides, organic acids, amino acids and fatty acids. In the presence of DSG and RSM, the growth of L. plantarum increased from 8.73 log CFU/mL to 13.86 log CFU/mL, at the end of 72 h. In comparison, when grown with commercial gum arabic (GA) and RSM, growth of L. plantarum reached a lower 11.49 log CFU/mL at 72 h. Metabolomics revealed that several metabolites, including lactose, depleted after fermentation, in the DSG and RSM treatment group, as compared to GA and RSM treatment group. This suggested that glycolysis were up regulated. This correlated with the increased growth, lactic acid, malic acid and fatty acids production by L. plantarum when it was grown on DSG and RSM. Next, the entire culture of L. plantarum with DSG and RSM was taken for spray drying, without the need to separate the bacteria from the culture media. DSG and RSM was able to stabilize L. plantarum, to remain viable at 10 log CFU/g after storage for 10 weeks. On the other hand, the viability was 8.8 log CFU/g when L. plantarum was spray dried with GA and RSM. This study demonstrated an innovative process and low-cost strategy to produce spray dried probiotic powder. DSG could be a potential low cost and sustainable replacement for GA, to develop other functional foods.